RETINAL LEAKAGE INDEX DYNAMICS ON ULTRA-WIDEFIELD FLUORESCEIN ANGIOGRAPHY IN EYES TREATED WITH INTRAVITREAL AFLIBERCEPT FOR PROLIFERATIVE DIABETIC RETINOPATHY IN THE RECOVERY STUDY. Issue 11 (November 2020) - Babiuch, Amy S.; Wykoff, Charles C.; Srivastava, Sunil K.; Talcott, Katherine; Zhou, Brenda; Hach, Jenna; Hu, Ming; Reese, Jamie L.; Ehlers, Justis P.
Abstract : Purpose: Characterization of leakage indices on ultra-widefield fluorescein angiography in proliferative diabetic retinopathy treated with intravitreal aflibercept. Methods: Prospective study enrolling subjects for treatment of proliferative diabetic retinopathy randomized 1:1 to receive 2-mg intravitreal aflibercept every 4 weeks (2q4) or every 12 weeks (2q12). Ultra-widefield fluorescein angiography images obtained at baseline, 24, and 48 weeks were analyzed using a semiautomated leakage segmentation platform. Panretinal and zonal leakage indices were calculated. Results: Forty eyes of 40 subjects were included, and mean age was 48 ± 12.1 years. Mean number of injections was 11 ± 1.7 in the 2q4 arm and 4 ± 0.4 in the 2q12 arm. Median baseline leakage index in the 2q4 and 2q12 groups was 5.1% and 4.3%, respectively ( P = 0.28). At 24 and 48 weeks, the 2q4 group significantly improved to 1.1% (−79%, P < 0.0001). At Week 24, the 2q12 group demonstrated nonsignificant improvement (3.4%; −21%, P = 0.47); by Week 48, improvement was significant (1.4%; −68%, P = 0.02). The 2q4 group resulted in lower leakage index compared with the 2q12 group at 24 weeks (1.1% vs. 3.4%, respectively; P = 0.008), but by 48 weeks, leakage index was similar between both groups (1.1% vs. 1.4%, respectively; P = 0.34). Conclusion: Proliferative diabetic retinopathy treated with intravitreal aflibercept demonstrated significant leakage index reductions at 1 year. Monthly dosing provided more rapid reduction in leakage index compared with quarterly dosing. Trial Registration: RECOVERY study (NCT02863354); https://clinicaltrials.gov/ct2/show/NCT02863354 . Abstract : Anti–vascular endothelial growth factor therapy demonstrates significant reduction in panretinal leakage index reduction measured on ultra-widefield fluorescein angiography in eyes with proliferative diabetic retinopathy at 1 year. Panretinal leakage index is a novel quantifiable imaging marker that may have a role for evaluating disease activity and progression.